Hvordan Forstå Fordommer? 2021
DOI: 10.18261/9788215041261-2021-08
|View full text |Cite
|
Sign up to set email alerts
|

8. Rom for ubehag i undervisning om rasisme i klasserommet

Abstract: Sammendrag Rasisme oppleves som et ubehagelig tema å snakke om. I kapittelet pekes det på pedagogiske fordeler ved å gi rom for ubehag i møte med rasisme. Ved å gi minoritets-og majoritetsstudenter like mye rom for å dele oppfatninger av rasisme, også de som er ubehagelige, kan man gi økt forståelse for rasisme og gode verktøy for å håndtere situasjoner knyttet til rasisme. Det tas utgangspunkt i erfaringer fra undervisning ved en norsk laererutdanning, der virtual reality ble anvendt som didaktisk metode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
2
0
6
Order By: Relevance
“…First, as stated, general antibullying programs do not succeed in reducing bias-based bullying (Bauer et al, 2007;Espelage et al, 2016), but programs assessing biasbased bullying specifically have shown promising effects (Brinkman et al, 2011). Second, it is emphasized elsewhere that students with minority backgrounds experience more discomfort with not being taken seriously than addressing racism as a topic within the classroom (e.g., Faye, 2021). The teachers' examples of how they handled the incidence of bias-based bullying in the situations referred to in the interviews could be interpreted as general bullying and are similar to what is found in other studies.…”
Section: Exploring the Potential Productivity In The Relationship Bet...mentioning
confidence: 99%
“…First, as stated, general antibullying programs do not succeed in reducing bias-based bullying (Bauer et al, 2007;Espelage et al, 2016), but programs assessing biasbased bullying specifically have shown promising effects (Brinkman et al, 2011). Second, it is emphasized elsewhere that students with minority backgrounds experience more discomfort with not being taken seriously than addressing racism as a topic within the classroom (e.g., Faye, 2021). The teachers' examples of how they handled the incidence of bias-based bullying in the situations referred to in the interviews could be interpreted as general bullying and are similar to what is found in other studies.…”
Section: Exploring the Potential Productivity In The Relationship Bet...mentioning
confidence: 99%
“…Til tross for at laerere og trenere kan vaere imot rasisme og til og med vaere engasjert i antirasistiske tiltak, kan de komme til kort enten på grunn av manglende kompetanse (Faye, 2021;Harlap & Riese, 2014) eller manglende institusjonell og strukturell støtte (Gillborn, 2004). Et første steg kan vaere å sette rasisme på dagsordenen i alle skoler og lag, og ikke bare på skoler, i klasser eller lag med elever/deltakere som har minoritetsbakgrunn.…”
Section: Må Gå Fra Vage Ord Til Handlingunclassified
“…Eriksen, 2021;Harlap & Riese, 2014;Osler & Lindquist, 2018;Røthing, 2015;Sibeko & Eriksen, 2022). Samtidig har fleire funne grunn til å åtvare mot at framstillingar av rasisme blir for eindimensjonale, med låste og reduserte posisjonar utan rom for nyanse (Eriksen, 2021;Faye, 2021).…”
Section: Innleiingunclassified
“…Så vil eg sjå litt naermare på to ulike undervisningskontekstar der ubehag kjem i spel. I den eine kjem ubehag i spel som ein del av eit planlagt undervisningsopplegg om rasisme, skildra av Faye (2021). I det andre tilfellet er det tanken på potensielt ubehag som påverkar korleis ein laerar forhandlar det å ta opp (eller unnlate å ta opp) kulturelle forskjellar (Åberg, 2021).…”
Section: Innleiingunclassified
See 1 more Smart Citation